“Sub-basins of the Wadi Al-Kuf basin, north of the Green Mountain”: A morphometric study: “Sub-basins of the Wadi Al-Kuf basin, north of the Green Mountain”: A morphometric study (jornal of the libyan geographical society, 2021)
The valleys of the Kuf basin are considered semi-arid basins on the northern slope of the Green Mountain. The basin occupies an area of ​​996 km and includes ninety (900) valleys, the most important of which are: (Wadi Beit Saleh, Wadi Sudan, Wadi Anbasa, Wadi Darqoush, Wadi Madiqa Al-Balout, Wadi Al-Jabarat, Wadi Al-Salb, Wadi Batah Al-Saq, Wadi Al-Rannana...). Their waters flow into the main valley and from there end in the Mediterranean Sea at Jirja Umma.Given the importance of the basin and the possibility of exploiting its natural resources, this study presents the morphometric characteristics of the basin. As is known, the study of morphometric characteristics is important in geomorphological studies and expresses the relationships between factors and processes and the phenomena that result from them. It is considered one of the characteristics of quantitative geomorphology in its general sense.The morphometric analysis of geometric and morphological properties was performed, adding drainage network characteristics. In this study, the researcher followed the quantitative graphical scientific method, relying on diaspora data from topographic and geological maps and forensic maps (DEM) using a geographic information systems program. (ArcGIS) and computer programs (Excel) were used to work on and schedule the data, process the region's database, and extract topographic and geological shapes and maps. The basin is currently developing in the early maturity stage.
Keywords: Morphometric; GIS; DEM